An Evaluation of Anxiety, Perceived Stress, and Coping Mechanisms among Nursing Students: A Cross-Sectional Correlational Analysis - Taghreed Hussien Aboelola (Journal of information systems engineering & management, 2025)
Background: This study aimed to investigate the relationship between anxiety, perceived stress, and coping strategies of nursing students at Northern Border University during their clinical training. Specifically, it sought to determine the (a) demographic profiles of the participants, (b) quantify of the prevalence and severity of anxiety and perceived stress among nursing students at different stages of their educational program, (c) identify and analyze the coping strategies employed by nursing students to manage anxiety and stress, determining which are most effective. Materials and Methods: This is a cross-sectional correlational descriptive study. The sample used has a balanced representation of genders, with a slight majority of female students (55.1%, 65 students) compared to male students (44.9%, 53 students). The students are distributed across the four academic years of their nursing program. The questions consider the students’ perceptions regarding anxiety, stress, and coping techniques, with multiple questions about their coping strategies and experiences, shows that a substantial 68.90% of students (agree or strongly agree) perceive the stress encountered during their education as a constructive element that contributes to their development as resilient nurses. Results: With 57.98% of students indicating that they use relaxation techniques, it is apparent that these strategies are a popular choice among nursing students for managing anxiety, particularly in high-pressure situations like exams and clinical practice. Clinical simulations and practical exams are identified as significant stressors by 77 students (64.7%) who agree or strongly agree that these contribute to their stress levels. Given the high stakes and practical nature of these assessments, it is understandable that they would induce anxiety. Conclusion: This perspective is crucial because it highlights how students can identify a silver lining within their challenges, protecting against the negative effects of stress. By reframing stress not merely as a hurdle to overcome but also as an opportunity for growth, students can develop resilience and a more positive outlook. For instance, a student preparing for a challenging exam might view the stress of studying as a chance to refine their time-management skills and deepen their understanding of the subject. Research has shown that adopting a growth mindset toward stress can enhance emotional well-being and improve performance in demanding situations. This underscores the importance of teaching students to reframe stressful experiences, not as threats to their well-being, but as valuable opportunities to learn, adapt, and thrive. Such a shift in perspective can foster long-term personal development and equip students with tools to navigate future challenges more effectively.